Recycling of rare earths: a critical review - Binnemans, Koen; Jones, Peter Tom; Blanpain, Bart; Van Gerven, Tom; Yang, Yongxiang; Walton, Allan; Buchert, Matthias (Journal of cleaner production, 2013)
The rare-earth elements (REEs) are becoming increasingly important in the transition to a green economy, due to their essential role in permanent magnets, lamp phosphors, catalysts, rechargeable batteries etc. With China presently producing more than 90% of the global REE output and its increasingly tight export quota, the rest of the world is confronted with a REE supply risk. Mining companies are now actively seeking new exploitable REE deposits while some old mines are being reopened. Because of the absence of economical and/or operational primary deposits on their territory, many countries will have to rely on recycling of REEs from pre-consumer scrap, industrial residues and REE-containing End-of-Life products. REE recycling is also recommended in view of the so-called “balance problem”. For instance, primary mining of REE ores for neodymium generates an excess of the more abundant elements, lanthanum and cerium. Therefore, recycling of neodymium can reduce the total amount of REE ores that need to be extracted. Despite a vast, mostly lab-scale research effort on REE recycling, up to 2011 less than 1% of the REEs were actually recycled. This is mainly due to inefficient collection, technological problems and, especially, a lack of incentives. A drastic improvement in the recycling of REEs is, therefore, an absolute necessity. This can only be realized by developing efficient, fully integrated recycling routes, which can take advantage of the rich REE recycling literature. This paper provides an overview of this literature, with emphasis on three main applications: permanent magnets, nickel metal hydride batteries and lamp phosphors. The state of the art in preprocessing of End-of-Life materials containing REEs and the final REE recovery is discussed in detail. Both pyrometallurgical and hydrometallurgical routes for REE separation from non-REE elements in the recycled fractions are reviewed. The relevance of Life Cycle Assessment (LCA) for REE recycling is emphasized. The review corroborates that, in addition to mitigating the supply risk, REE recycling can reduce the environmental challenges associated with REE mining and processing. ► Less than 1% of rare earths in end-of-life consumer products are being recycled. ► Recycling can help to ensure a supply of the most critical rare earths. ► Valuable waste streams are magnets, metal hydride batteries and lamp phosphors. ► Recycling of neodymium avoids overproduction of cerium and lanthanum. ► Recycling and primary mining of rare earths are complementary activities.